Analysis of Net Interest Margin (NIM) and Return on Assets (ROA) - Ajeng Ayu Wardhani Putri; Nor Norisanti; Faizal Mulia Z (Almana : Jurnal Manajemen dan Bisnis, 2021)
In 2018 the banking sector experienced a very fast expansion resulting in a decrease in the Capital Adequacy Ratio (CAR) at the level of 22.01% compared to 2017, namely 22.75%. Growth in risk-weighted assets (RWA) was the cause of the decline in the value of the Capital Adequacy Ratio (CAR) which can be influenced by aspects of financial performance, one of which is the profitability aspect of Net Interest Margin (NIM) and Return On Assets (ROA). This study aims to determine the effect of Net Interest Margin (NIM), Return On Assets (ROA) on the Capital Adequacy Ratio (CAR) in 31 private banks listed on the Indonesia Stock Exchange (IDX). The method used is multiple linear regression analysis using IBM SPSS 24. Based on the results of the study showed a significant influence between Net Interest Margin (NIM), Return On Assets (ROA) on the Capital Adequacy Ratio (CAR) together (simultaneously).